2018
DOI: 10.15419/jmri.108
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid-Induced Hyperammonemia with Encephalopathy (VIHE): A Case Report

Abstract: Valproic acid (VPA) is a wide spectrum antiepileptic medication indicated for seizure prophylaxis across the spectrum of epilepsy. Since coming into clinical use, VPA has also been recommended for the management of a variety of other pathologies, including, most notably, mood stabilization in the manic patient.VPA's common adverse effects include gastrointestinal, influenza-like symptoms, headache, and difficulties with sleep; nonetheless, in rare instances, VPA has been noted to cause the severe and potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Up to 50% cases can be asymptomatic. 1 Treatment for valproate induced encephalopathy is mainly supportive along with withholding valproate. The aim is to reduce ammonia production by stopping catabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 50% cases can be asymptomatic. 1 Treatment for valproate induced encephalopathy is mainly supportive along with withholding valproate. The aim is to reduce ammonia production by stopping catabolism.…”
Section: Introductionmentioning
confidence: 99%
“…1 VIHE, presenting with lethargy, confusion, frank delirium, blurred vision, seizures, or coma, is most commonly treated by discontinuing the drug and adding a substance to diminish ammonia levels, including lactulose or rifaximin/neomycin; however, current research has proposed mechanisms of prevention, treatment, and maintenance therapy to allow for the continuation of VPA using supplementation of levocarnitine or carglumic acid. [2][3][4][5] Studies have shown that individuals with a past medical history of VIHE may continue VPA with the addition of supplementation, but continuation of VPA without supplementation in a patient with a past medical history of VIHE has not previously been reported.…”
mentioning
confidence: 99%